Pengaruh Pengawasan Dan Disiplin Kerja Terhadap Kinerja Karyawan Rumah Sakit Karya Husada Cikampek - Hilda Kartini Rusmayanti; Anwar Musadad (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to examine and analyze the effect of supervision and work discipline on employee performance at Karya Husada Hospital Cikampek. The research was conducted using descriptive and verification methods, namely: collecting, presenting, analyzing and testing hypotheses and making conclusions and suggestions. Samples were collected using the Slovin formula, as well as probability sampling technique with simple random sampling which then produced 182 samples from a population of 333 people. The analytical technique used is the technique of scale range analysis and path analysis with the help of the Method of Successive Interval (MSI) computer program Microsoft Excel 2010 and the SPSS version 23 application. a value of 0.768 which means it has a strong, positive and significant correlation level between Supervision and Work Discipline. The partial effect of Supervision on Employee Performance is 0.330 which is smaller than Work Discipline whose value is 0.366. So it can be stated that supervision contributes less to employee performance compared to work discipline. The simultaneous effect of Supervision and Work Discipline on Employee Performance is 69.6% while the remaining 30.4% is another variable that was not examined.